The interactions between Al‐/Fe‐(hydr)oxides and soil organic carbon mediate the aggregation of yellow soils. (15th June 2022) - Di, Xinyue; Xiao, Baohua; Tang, Haiming; An, Xianjin
Abstract: Soil aggregates are essential for improving soil permeability and reducing soil erosion. Still, in high oxide soils, the roles of soil organic carbon (SOC) and Al‐/Fe‐(hydr)oxide in soil aggregation are unclear, which limits our ability to predict how soil aggregation responds to soil management and climate change. In this study, soil samples were collected from three depths of a yellow soil profile (0–12 cm, 12–24 cm and 24–36 cm) and fractionated into aggregates by wet sieving. Organic carbon (OC) and Al‐/Fe‐(hydr)oxide contents of aggregates were determined. We found that the relationships of OC and Al‐/Fe‐(hydr)oxide to aggregate size were depth‐dependent. OC concentrations increased and decreased at 0–12 cm and 24–36 cm depth soils, respectively, as aggregate size decreased. The OC/(Fe + Al) ratios of aggregates suggest that organic carbon will form multi‐layer and mono‐layer coatings on Al‐/Fe‐(hydr)oxide in the 0–12 cm and 24–36 cm depth soils, respectively. This leads to steric hindrances of OC and electrostatic repulsion of Al‐/Fe‐(hydr)oxide at two depths, respectively, and further influenced the aggregation. Based on these findings, we proposed a mechanism in which aggregates are formed by OC and Al‐/Fe‐(hydr)oxide association with the appropriate OC/(Fe + Al) ratio. This mechanism focuses on the role of the OC/(Fe + Al) ratio mediated in soil aggregation. It can account for the inconsistent responses of aggregation and SOC sequestration to exogenous OC addition in field experiments. Further studies are needed and will be helpful to calculate the dose of organic application for formulating healthy and sustainable soil management.